Determinants of the non-performing loan ratio in the European Union banking sectors with a high level of impaired loans - Ciukaj, Radosław; Kil, Krzysztof (Economics and Business Review, 2020)
In the article an attempt is made to identify the quality of credit exposure determinantsof banks in European Union countries that were characterized by a high levelof impaired loans at the end of 2017 (Bulgaria, Croatia, Cyprus, Italy, Ireland, Greece,Portugal). Using the static panel-based approach the non-performing loan (NPL) determinantsfor the period from 2011 to 2017 were analyzed. The results showed thatthe high level of NPLs can be explained mainly by both macroeconomic and microeconomicfactors. In particular, it has been shown that in the surveyed countries supervisoryauthorities should pay special attention to smaller banks with high dynamics ofnew loans and a low return on assets due to the fact that these entities are characterizedby a higher NPL ratio. A higher level of NPL is also affected by a high concentrationof the banking sector and higher interest rates on newly granted loans. As a resultof research it was also shown that the majority of NPL determinants are the same inall types of banks, regardless of the business model and the scope of banking supervision.The differences were noticeable in characteristics regarding the housing marketas well as the profitability of operations and lending dynamics of the analyzed entities.